ANALISIS PERBANDINGAN METODE SPRINGATE (S-SCORE) DAN ZMIJEWSKI (X-SCORE) DALAM MEMPREDIKSI KEBANGKRUTAN PERUSAHAAN (Studi Pada Perusahaan Tekstil dan Garmen Yang Terdaftar di Bursa Efek Indonesia Selama Periode 2018 - 2020) - Luthfi Tri Hardina; Maria Yovita R Pandin (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2021)
This study aims to determine whether there are differences in the results of predicting bankruptcy of textile and garment companies on the IDX using the Springate and Zmijewski methods in 2018-2020 and to find out which prediction model is the most accurate. The sample used in this study were 8 textile and garment companies listed on the IDX. The sampling technique was determined by purposive sampling method. The type of data used is secondary data with data collection using the method of documentation and literature study. The data analysis technique used is the Kruskal-Wallis H test and the level of accuracy test. The results of this study indicate that there is a significant difference between the Springate and Zmijewski methods using the Kruskal-Wallis H test. Then, the most accurate predictive methods in predicting the bankruptcy of textile and garment companies is Zmijewski with an accuracy rate of 88%.